1975
DOI: 10.1172/jci108063
|View full text |Cite
|
Sign up to set email alerts
|

Control and localization of rat adrenal cyclic guanosine 3', 5'-monophosphate. Comparison with adrenal cyclic adenosine 3', 5'-monophosphate.

Abstract: A B ST R A CT Cyclic AMP and cyclic GMP were measured in rat adrenal glands after either hypophysectomy alone or after hypophysectomy and treatment with ACTH. Adrenal cyclic GMP levels rise in acutely hypophysectomized rats to a maximum at 1 h of ap- about 1 pmol per mg tissue for 7 days, adrenal cyclic GMP showed a biphasic rhythm in long-term hypophysectomized animals. After an initial peak at 1 h after hypophysectomy, adrenal cyclic GMP declined to baseline at 4-12 h but thereafter progressively rose with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

1976
1976
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…A rise in cyclic GMP during hormone stimulation was described by Sharma et al [9], who reported that ACTH stimulated both cyclic GMP synthesis and corticosterone production in adrenal cells at concentrations which did not cause a measurable increase in synthesis of cyclic AMP. Such observations are not consistent with the report of Whitley et al [19], who demonstrated that ACTH reduces cyclic GMP levels in the adrenal. Stimulation of cyclic GMP levels in ovarian tissue has been reported to occur after administration of gonadotropin subunits to superovulated female rats [20].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…A rise in cyclic GMP during hormone stimulation was described by Sharma et al [9], who reported that ACTH stimulated both cyclic GMP synthesis and corticosterone production in adrenal cells at concentrations which did not cause a measurable increase in synthesis of cyclic AMP. Such observations are not consistent with the report of Whitley et al [19], who demonstrated that ACTH reduces cyclic GMP levels in the adrenal. Stimulation of cyclic GMP levels in ovarian tissue has been reported to occur after administration of gonadotropin subunits to superovulated female rats [20].…”
Section: Discussioncontrasting
confidence: 96%
“…The actions of estrogen upon the rat uterus have been shown to include stimulation of tissue levels of cyclic GMP [ 16]. Also, insulin has been reported to raise the level of cyclic GMP in liver cells [18], and ACTH has been shown to suppress cyclic GMP levels in the rat adrenal [19]. However, there is conflicting data about the actions of trophic hormones upon cyclic GMP formation in steroidogenic target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, immunofluorescent staining has shown that cAMP and cGMP have distinct staining patterns in a variety of cell types. 34,35 cAMP is largely confined to cytoplasmic domains, with very little nuclear staining, whereas cGMP is found in nuclei, with some cytoplasmic localization. In addition, a nuclear guanylyl cyclase has been identified in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro system like ours the intracellular concentration of cAMP during TSH stimulation is mostly more than 1000 times that of the incubation medium. Cyclic AMP is believed not to be confined to any cell organdíes but seems to reside in the cytoplasm (Whitley et al 1975). Therefore the cell membrane should be the structure that maintains the concen¬ tration gradient.…”
Section: Discussionmentioning
confidence: 99%